Improved nutrition and resilience will make conservation agriculture more attractive for Zambian smallholder farmers - Mhlanga, Blessing; Mwila, M.; Thierfelder, Christian L. (Cambridge University Press, 2021)
Food and nutrition insecurity in southern Africa call for improvements in traditional agriculture systems. Conservation Agriculture (CA) based on minimum soil disturbance, permanent soil cover and crop diversification has been implemented as a strategy to maintain yields while safeguarding the environment. However, less focus has been placed on potential synergistic benefits on nutrition security. Maize-based systems may increase household income through selling but may not lead to proportionate reduction in malnutrition. Crop diversification in CA systems can have a direct impact on the nutritional status of farm households due to improved dietary diversity. Here we assess how the integration of grain legumes, cowpeas and soybeans, in maize-based CA systems either as intercrops or rotational crops affects maize grain yield and stability, total energy yield, protein yield and surplus calories after satisfying the daily requirement per household. The experiments were carried out from 2012 to 2020 (nine consecutive cropping seasons) in six eastern Zambian on-farm communities using 966 observations. Results show that intercropping compromises maize yields with marginal yield penalties of −5% compared to no-till monocropping. However, intercropped yields were more stable across environments. Total system caloric energy and protein yield were highest in intercropping systems due to higher productivity per unit land area owing to the additive contribution of both maize and legumes. Total system caloric energy and protein yield reached yearly averages of 60 GJ ha−1 and 517 kg ha−1, respectively, for the intercropping system as compared to 48 GJ ha−1 and 263 kg ha−1 in monocropped maize systems. Tillage-based monocrop resulted in the least stable yields. Our results suggest that intercropping maize with grain legumes in CA systems is a promising option for smallholder farming households to improve dietary diversity, dietary quality and stability of yields thus contributing to sustainable agriculture intensification while maintaining food and nutrition security.